Biotransformations in organic chemistry : a textbook - Faber, K. (Kurt), 1953- (Berlin ; New York : Springer-Verlag, 2004)
After a basic introduction spanning the principles of stereoselective transformations, kinetics and enzyme properties, the different types of reactions are explained. Special techniques, such as the use of enzymes in organic solvents, immobilization techniques and the use of modified enzymes, are also treated. This new edition features an improved didactic style and includes new developments, such as dynamic resolution, stereo-inversion and enantio-convergent processes.
Includes bibliographical references and index.
Keywords: Enzymes -- Biotechnology; Biotransformation (Metabolism); Organic compounds -- Synthesis